The Influence Of Inflation On The Vital Activity Of A Society In The Conditions Of A Dynamically Developing Economy - Dj. Zaynalov; S. Aliyeva (Фінансовий простір, 2018)
In  this  article,  the  authors  show   the  consumer  price  index  (CPI)  as  the  main  indicator of inflation in the consumer sector of the counry. It is noted that in dynamically developing conditions, inflation is most clearly expressed and determined by the increase in prices. The  scheme  for  calculating  the  consumer  price index  and  inflation  index  through  the  relationship between them is shown and justified.